Analytical Exposition Materials on WordPress for Eleventh Grade Students of Senior High School (a Research and Development Research) - Dina Rachmawati; Siti Hikmah; Bintang Suherlan (Journal of English Language Studies, 2019)
Abstract           The objectives of this research were: first, to determine students’ learning needs for Analytical Exposition materials; Second, to figure out the process of product development of Analytical Exposition Materials on WordPress; Third, to investigate the content quality of the developing product based on 2013 curriculum. Research and Development design was used in conducting the research. Six steps of R&D cycle by Gall & Borg was employed in product development. The steps were: first, research and data gathering; second, planning; third, developing preliminary form of a product; fourth, preliminary field testing; fifth, revising main product; sixth, main field testing. Accordingly, this research revealed that first, ICT – based teaching-learning media was needed for Analytical Exposition lesson. Second, the processes of product development through the sixth steps of R&D cycle were run well. Third, the content quality of the product was good and in lined with 2013 curriculum. By all means, the developed product proved to be suitable as ICT-based teaching-learning media and meet the standard requirement of 2013 curriculum. Keywords: Analytical Exposition Text; Teaching-Learning Media; 2013 Curriculum